Relationship of Pay and Job Satisfaction (European Journal of Marketing and Economics, 2020)
The study measures the relationships of pay satisfaction and its dimensions (pay level, benefits, pay raises and administration/structure) with job satisfaction. A total of 200 public sector employees, from different companies and non-governmental, independent institutions participated. The results showed that overall pay satisfaction and pay level affected job satisfaction while pay raises, benefits and administration/structure did not. The results and limitations of the study were discussed and suggestions on future research were given.
Keywords: pay satisfaction, pay level, benefits, pay raise, administration, structure, job satisfaction .